Inventory Information System Using Fifo And Holt Winters Multiplicative Methods - Firmansyah, Verdi Tri; Anik Vega Vitianingsih; Syahadiyanti, Litafira; Pamudi; Alda Raharja (Sinkron : jurnal dan penelitian teknik informatika, 2024)
In the era of society 5.0, information technology plays an important role in daily life, company operations, and management. Medium-scale stores such as Nisrina Mart require an inventory control process to determine the number of products to be restocked quickly and accurately. However, what happened was the opposite, shop owners experienced a lot of losses because the inventory control process carried out manually had the potential to experience inaccurate data and material losses. Based on these problems, this research tries to propose the development of an inventory information system for reporting incoming and outgoing goods using the First In First Out (FIFO) method. Stock forecasts based on previous sales data are generated to project future stock needs using the Holt-Winters Multiplicative trend moment method. The software development model uses a waterfall which includes requirements, design, implementation, testing, and maintenance. The test results of the Holt Winter multiplication method show a prediction error rate of 0.27. Meanwhile, the level of accuracy in predicting goods sales is 73%. The implementation of this information system is expected to provide convenience in stock monitoring, reduce prediction errors, and increase the accuracy of product data analysis reports to support more effective and efficient management decision-making.